Evaluating the validity of testimony: The role of the order of evidence - Henry Otgaar; Tamara L.F. De Beuf; Melanie Sauerland; Alexa Schincariol (Forensic Science International: Synergy)
Legal practitioners sometimes ask psychologists to evaluate the validity of statements of victims, witnesses, and suspects. For their assessment, psychologists often have access to different pieces of evidence (e.g., a video recording of the interview, the suspect's statements). Research has demonstrated that the order of reviewing the evidence can affect decision-making. To examine expert witnesses' views about this, we surveyed 52 legal psychologists about their preferred order for considering the evidence in a statement validity assessment in a fictional sexual abuse case. The assessment was about the validity of the statement of the alleged child victim. The case file included the following documents: an audiovisual recording of the child interview at the police station, a verbatim transcript of that same interview, and a written statement of the suspect. Legal psychologists indicated their preferred order for reviewing these documents and explained the rationale behind their choice. There was no uniform approach among legal psychologists. About one third of respondents would first examine the audiovisual recording, then the verbatim transcript and finally the suspect's statement. In contrast, about one third would first look at the verbatim transcript, then at the recording and last at the suspect's statement. These differences in approach likely highlight the challenges and trade-offs entailed in deciding on the optimal order and emphasize the need for a discussion in the expert witness community about these issues.